Effects of Vojta Therapy on Postural control and Gait characteristics in Chronic Stroke Survivor: A review article - Saelao, Benjawan; Khobkhun, Fuengfa; Suttiwong, Jatuporn (Journal of Thai Stroke Society, 2023)
Vojta therapy is a physical therapy technique that relies on the principle of reflex locomotion stimulation of the neurophysiological system. This technique induces reflex movement by the therapist to apply force to a specific area (specific zone). Recently, Vojta therapy has been shown to stimulate brain activity in the supplement motor areas, premotor areas, superior parietal cortex, and posterior cingulate cortex. It is believed that Vojta therapy could promote posture, balance, and walking in stroke survivors. Therefore, this review article aimed to comply with the study of Vojta therapy in chronic stroke survivors, which is a specific technique that must be practiced and has contraindications and cautions in this group of patients. However, few studies were found in the last two decades. This technique should be applied as a treatment and in clinical applications in the future.